The Browning version (Janus Films, 1951)
Redgrave portrays Andrew Crocker-Harris, an embittered, middle-aged schoolmaster who begins to feel that his life has been a failure. Diminished by poor health, a crumbling marriage, and the derision of his pupils, the once brilliant scholar is compelled to reexamine his life when a young students offers an unexpected gesture of kindness. A heartbreaking story of remorse and atonement.